Analisis Perkembangan Penelitian Baja Kekuatan Tinggi Dalam Struktur Sipil Berbasis Bibliometric Mapping - Bima Ahmad Fathoni; Muhammad Kahfi Rananda; Andre Wibowo; Taufiq Hidayatullah Limbong (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the development of research on high-strength steel (HSS) in civil structures using a bibliometric mapping approach. Data were collected from the Scopus database, resulting in 12,206 publications. The analysis includes publication trends, keyword co-occurrence, citation analysis, and co-authorship networks, visualized using VOSviewer. The results indicate a significant increase in publications in recent years, reflecting growing global interest in HSS. The conceptual structure reveals five main research clusters: structural behavior, extreme loading, material durability, sustainability, and numerical modeling. Despite this growth, the research landscape remains fragmented and predominantly focused on technical aspects. Emerging topics such as sustainability and life cycle assessment suggest a shift toward more environmentally oriented research. In addition, scientific collaboration is still concentrated within certain regions. This study highlights the need for a more integrated and multidisciplinary approach to advance HSS research in civil engineering.